Pengujian Model Pengaruh Tata Kelola TI Terhadap Transformasi Digital dan Kinerja Asuransi B - Rizka Putri Wahyuni; Rahmat Mulyana; Lukman Abdurrahman (JURIKOM (Jurnal Riset Komputer), 2022)
The emergence of emerging technology disruptions, changes in stakeholder behavior towards digital, coupled with the Covid-19 pandemic has forced various incumbent organizations to transform digitally (TD). There are still many investments related to TD that fail to achieve the expected expectations due to the alleged lack of good governance implementation. Previous studies have examined the significant role of information technology (IT) on organizational performance. However, it is suspected that traditional IT Governance (TKTI) practices are not necessarily effective in the digital era. Only a few have examined the effect of IT governance (TKTI) on TD, and no one has examined the effect of TD on organizational performance (KO). Therefore, this study aimed to validate the effect of hybrid TKTI mechanisms (traditional and agile/adaptive) on TD, as well as the effect of TD on knockouts and their performance achievements through a balanced scorecard (BSC) perspective. The research method used is a survey by distributing Likert-scale online questionnaires to 11 roles related to BP in Asuransi B and succeeded in getting 50 relevant respondents. Data from the results of filling out the questionnaire were analyzed with the help of SmartPLS 3.0 tools. The test is carried out using Structural Equation Modeling (SEM) with a formative model, in the form of testing the inner model and outer model. The test results of this study indicate that both traditional and agile/adaptive TKTI mechanisms have a significant positive effect on BP. Then TD also proved to have a significant positive effect on KO. This research contributes to the knowledge base for further research on related topics, and can be an implementation reference to oversee the success of TD for practitioners, especially in the context of the insurance industry